Advances in two-dimensional heterostructures by mono-element intercalation underneath epitaxial graphene. Issue 3 (August 2021) - Wu, Songhao; Zhang, Quanzhen; Yang, Huixia; Ma, Yuanxiao; Zhang, Teng; Liu, Liwei; Gao, Hong-Jun; Wang, Yeliang
Abstract: Two-dimensional (2D) materials have displayed many remarkable physical properties, including 2D superconductivity, magnetism, and layer-dependent bandgaps. However, it is difficult for a single 2D material to meet complex practical requirements. Heterostructures obtained by vertically stacking different kinds of 2D materials have extensively attracted researchers' attention because of their rich electronic features. With heterostructures, the constraints of lattice matching can be overcome. Meanwhile, high application potential has been explored for electronic and optoelectronic devices, including tunneling transistors, flexible electronics, and photodetectors. Specifically, graphene-based van der Waals heterostructures (vdWHs) by intercalation are emerging to realize various functional heterostructures-based electronic devices. Intercalating atoms under epitaxial graphene can efficiently decouple graphene from the substrate, and is expected to realize rich novel electronic properties in graphene. In this study, we systematically review the progress of the mono-element intercalation in graphene-based vdWHs, including the intercalation mechanism, intercalation-modified electronic properties, and the practical applications of 2D intercalated heterostructures. This work would inspire edge-cutting ideas in the scientific frontiers of 2D materials.